Influences of Lactiplantibacillus plantarum dy-1 Fermentation on the Bitterness of Bitter Melon Juice, the Composition of Saponin Compounds, and Their Bioactivities - Juan Bai; Zihan Yang; Wei Luo; Ying Zhu; Yansheng Zhao; Beibei Pan; Jiayan Zhang; Lin Zhu; Shiting Huang; Xiang Xiao (Foods)
Lactic acid bacteria fermentation is a beneficial bioprocessing method that can improve the flavor, transform nutrients, and maintain the biological activity of foods. The aim of this study is to investigate the effects of Lactiplantibacillus plantarum dy-1 fermentation on the nutritional components, flavor and taste properties, and composition of saponin compounds and their hypolipidemic and antioxidant activities. The results suggested that the total polyphenol content increased, and the soluble polysaccharides and total saponin contents decreased in fermented bitter melon juice (FJ) compared with those in non-fermented bitter melon juice (NFJ). The determination of volatile flavor substances by GC-MS revealed that the response values of acetic acid, n-octanol, sedumol, etc., augmented significantly, and taste analysis with an electronic tongue demonstrated lower bitterness and higher acidity in FJ. Furthermore, UPLC-Q-TOF-MS/MS testing showed a significant decrease in bitter compounds, including momordicines I and II, and a significant increase in the active saponin momordicine U in the fermented bitter melon saponin group (FJBMS). The in vitro assays indicated that FJBMS exhibited similar antioxidant activities as the non-fermented bitter melon saponin group (NFBMS). The in vitro results show that both NFBMS and FJBMS, when used at 50 μg/mL, could significantly reduce fat accumulation and the malondialdehyde (MDA) content and increased the catalase (CAT) activity, while there was no significant difference in the bioactivities of NFBMS and FJBMS. In conclusion, Lactiplantibacillus plantarum dy-1 fermentation is an effective means to lower the bitterness value of bitter melon and preserve the well-known bioactivities of its raw materials, which can improve the edibility of bitter melon.